POSSIBLE WAYS OF FOOD CONTAMINATION - Qaxxorov Faxriddin Baturbekovich; Issakov Shokir Allaberdi o’g’li; Muldabekova Bayan Jaksilykovna; Shingisov Azret Utebayevich (Лучшие интеллектуальные исследования, 2024)
Abstract: In this article, possible indicators of contamination of food products are mentioned. That is, through this, we can learn about the decrease in nutritional quality indicators of food products.